Prediction of mortality in secondary peritonitis: a prospective study comparing p-POSSUM, Mannheim Peritonitis Index, and Jabalpur Peritonitis Index - Akshant Anil Pathak; Vivek Agrawal; Naveen Sharma; Karan Kumar; Chinmay Bagla; Aakash Fouzdar (Perioperative Medicine, 2023)
Abstract Background Risk scoring systems are required to allow accurate prognostication, compare outcomes of surgery, and allow patients to make informed decisions about their health. This prospective study compares the p-POSSUM (Portsmouth Modification to Physiological and Operative Severity Score for Enumeration of Mortality), Mannheim Peritonitis Index, and Jabalpur Peritonitis Index for their utility in predicting mortality in patients with peritonitis. Methods Perioperative data was collected from 235 patients with secondary peritonitis and used to calculate p-POSSUM, MPI, and JPI scores. The accuracy of the 3 scores was compared using receiver operator characteristic curves. Results p-POSSUM and Mannheim Peritonitis Index were similar in their accuracy with area under the curve (AUC) values of 0.756 and 0.757. Jabalpur Peritonitis Index had an AUC of 0.665. Conclusion p-POSSUM and Mannheim Peritonitis Index can be used to predict mortality in patients with secondary peritonitis. Jabalpur Peritonitis Index is not suited for this purpose. Further studies are required to improve the diagnostic performance of p-POSSUM and MPI in patients with secondary peritonitis.